Principles of Accounting. (Book Review). - Meyer, Philip E.; Tuttle, Roy E. (The Accounting Review, 1981)
Reviews the book "Principles of Accounting," by Belverd E. Needles Jr., Henry R. Anderson and James C. Caldwell.